2013
DOI: 10.4269/ajtmh.12-0591
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the CCR-5/MIP-1 α Axis in the Pathogenesis of Rocio Virus Encephalitis in a Mouse Model

Abstract: Abstract. Rocio virus (ROCV) caused an outbreak of human encephalitis during the 1970s in Brazil and its immunopathogenesis remains poorly understood. CC-chemokine receptor 5 (CCR5) is a chemokine receptor that binds to macrophage inflammatory protein (MIP-1 α). Both molecules are associated with inflammatory cells migration during infections. In this study, we demonstrated the importance of the CCR5 and MIP-1 α, in the outcome of viral encephalitis of ROCV-infected mice. CCR5 and MIP-1 α knockout mice survive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
(29 reference statements)
0
13
0
2
Order By: Relevance
“…In two previous studies, we characterized partially the immune response to ROCV infection [ 2 , 3 ]. Here, to better understand the immunopathologic process, we infected BALB/c mice with 1.10 6 PFU ROCV, sacrificed these animals at 5 and 7 days post-infection (p.i.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two previous studies, we characterized partially the immune response to ROCV infection [ 2 , 3 ]. Here, to better understand the immunopathologic process, we infected BALB/c mice with 1.10 6 PFU ROCV, sacrificed these animals at 5 and 7 days post-infection (p.i.)…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies from our group demonstrated that ROCV infects and induces in BALB/c mice damage of the central nervous system (CNS), characterized by neuronal degeneration and apoptosis with detectable levels of inflammatory cytokines and massive cellular infiltration [ 2 ]. Moreover, cellular infiltration in CNS is highly dependent of the CCR-5/MIP-1α axis, since CCR5 and macrophage inflammatory protein 1 alpha (MIP-1α) knockout mice presented reduced inflammation with increased survival rates after ROCV infection [ 3 ]. CNS cellular infiltration induced by ROCV infection is characterized by F4/80 + cells, detected early as 4 days post-infection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the knockout mice required a higher lethal dose than those mice of the wild type. The CCR5/MIP-1α axis may contribute to the migration of cells into ROCV infected brains [27]. These findings can help to better understand the pathogenesis and the physiopathology of the human meningoencephalomyelitis by ROCV and other flaviviruses of the JE serocomplex.…”
Section: Rocio Virus (Rocv)mentioning
confidence: 96%
“…The first cases of Rocio virus (ROCV) were recorded in the southeastern region of Brazil during a viral encephalitis epidemic that lasted for about 2 years in the 1970s. Although subsequent outbreaks did not occur, there was serological evidence of ROCV circulation, which serves as a warning signal for possible new epidemics (37). La crosse virus (LACV) is present in Latin America and in some regions of North America and is transmitted by mosquitoes of the genus Aedes.…”
Section: Origin Of the Main Arboviruses That Cause Human Diseases Andmentioning
confidence: 99%